Strategi Adaptasi Narapidana Lansia dalam Lingkungan Pemasyarakatan di Lapas Kelas I Tangerang - Candra Aditya Kurniawan; Febri Birrul Walidaini; M. Naufal Andika Pahlevi (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
The correctional system in Indonesia faces challenges with the increasing number of elderly prisoners with special needs, especially in terms of health, psychology, and social aspects. This study aims to identify adaptation strategies used by elderly prisoners in Tangerang Class I Prison using a qualitative approach through interviews, observations, and documentation analysis. The results showed that elderly prisoners adapt by building social relationships, participating in rehabilitation programs, and relying on support from officers. Psychological factors such as self-acceptance and mental resilience play an important role in this process. However, limited health facilities and the lack of special programs for the elderly are major obstacles. This study is expected to be the basis for developing more inclusive correctional policies to improve the welfare of elderly prisoners during their sentence.